Distributed Strain Sensor Networks for In-Construction Monitoring and Safety Evaluation of a High-Rise Building. (27th September 2012) - Ye, X. W.; Ni, Y. Q.; Xia, Y. X.
Abstract : The New Headquarters of Shenzhen Stock Exchange (NHSSE), currently being constructed in Shenzhen, China, is a high-rise building with a height of 245 m. One salient feature of NHSSE is its huge floating platform with an overall plan dimension of 98 m × 162 m and a total height of 24 m, making it one of the largest cantilever structures in the world. In recognition of the uniqueness of the floating platform, a long-term structural health monitoring (SHM) system has been designed and implemented by The Hong Kong Polytechnic University for both in-construction and in-service monitoring of NHSSE. As part of this monitoring system, 224 vibrating-wire strain gauges have been permanently installed to measure the strain responses of key structural components of the floating platform. A wireless strain monitoring system by integrating local tethered data acquisition and long-range wireless data transmission has been developed for real-time strain monitoring and visualization. This paper presents the stress evolution of the floating platform during dismantlement of temporary supports on the basis of the real-time monitoring data and the statistical stress analysis and safety evaluation of the floating platform by use of the long-term monitoring data, as well as the effect of the welding residual stress on structural safety of NHSSE.